Bean resistance to the attack of pod weevil Apion spp. - Garza García, Ramón (2016)
During 1990, 218 bean landraces were grown under rainfall conditions in Santa Lucia de Prias, Mexico, to evaluate its reaction to the attack of pod weevil bean (Apion spp.). The bean plants were exposed to natural pressure of the insect. At the end of the growing season, samples of 30 pods were taken in two replicates and the percentage of damaged pods was quantified. A scale of qualification was used for determining the degree of resistance. Fourty one bean landraces were classified as resistant, which Hgo-19-A, Hgo-40-A, Hgo-51, Tlax-65-A, Jal-112 y Mex-49 were outstanding. The susceptible control cultivars, Canario 107 and Bayomex, showed 38 and 52 percent of damaged pods, respectively.